A PERSONAL PROOF OF THE STOKES' THEOREM

:
Leonardo Rubino leonrubino@yahoo.it February 2012 For www.vixra.org

Abstract: in this paper you will find a personal, practical and direct demonstration of the Stokes’ Theorem. The Stokes’ Theorem (practical proof-by Rubino!): If we have a volume, we can hold it as made of many small volumes, as that in Fig. 1; for every small volume, the following holds: (and so it holds also for the whole volume…) y
dz -dx -dy dy dx -dz 0 Walk dl

z

r B

r r r r r r r B ⋅ d l = rot B ⋅ d S = ∇ ∫ ∫ ∫ × B ⋅ dS
l S S

r

x

Fig. 1: For the Stokes’ Theorem (proof by Rubino). r r Let’s figure out B ⋅ dl : On dz B is Bz; on dx B is Bx; on dy B is By; ∂Bz ∂B dx − z dy , for 3-D Taylor’s development and also because to go ∂x ∂y from the center of dz to that of –dz we go up along x, then we go down along y and nothing along z itself. ∂B ∂B ∂B ∂B Similarly, on -dx B is B x − x dz + x dy and on -dy B is B y − y dx + y dz . ∂x ∂z ∂z ∂y By summing up all contributions: on -dz B is B z + r r ∂B ∂B ∂B ∂B B ⋅ dl = Bz dz − ( B z + z dx − z dy )dz + Bx dx − ( B x − x dz + x dy )dx + By dy − ∂x ∂y ∂z ∂y ∂B ∂B ∂B y ∂B ∂B ∂B ∂B ∂B dx + y dz )dy = ( z − y )dydz + ( x − z )dxdz + ( y − x )dxdy = + (B y − ∂y ∂z ∂z ∂x ∂x ∂y ∂x ∂z r r v r r r ˆ (dydz ) , y ˆ (dxdz ) , z ˆ (dxdy ) ] whereas here dS has got components [ x = rotB ⋅ dS = ∇ × B ⋅ dS that is, the statement: r r r v r r r B ⋅ d l = rot B ⋅ d S = ∇ ∫ ∫ ∫ × B ⋅ dS , after having reminded of:
l S S

ˆ x r r r ∂ rotB = ∇ × B = ∂x Bx

ˆ y ∂ ∂y By

ˆ z ∂ . ∂z Bz ---------------------------------

Appendix) Divergence Theorem (a well known and practical proof): y
dz B C F G

r E
D H E

∫ E ⋅ dS = ∫ divE ⋅ dV
S V

r

r

r

dy

0

A

dx

x Fig. 2: For the Divergence Theorem.

r Name φ the flux of the vector E ; we have: r r dφABCD = E ⋅ dS = − Ex ( x, y, z )dydz ( y means y “mean”) dφEFGH = Ex ( x + dx, y , z )dydz , but we obviously know that also: (as a development): ∂E ( x, y , z ) Ex ( x + dx, y , z ) = Ex ( x, y , z ) + x dx so: ∂x ∂E ( x, y, z ) dφEFGH = Ex ( x, y, z )dydz + x dxdydz and so: ∂x ∂E dφ ABCD + dφ EFGH = x dV . We similarly act on axes y and z: ∂x ∂E dφ AEHD + dφBCGF = y dV ∂y ∂E dφ ABFE + dφCGHD = z dV ∂z And then we sum up the fluxes so found, having totally: r r r ∂E y ∂Ez ∂E dφ = ( x + )dV = (div ⋅ E )dV = (∇ ⋅ E )dV therefore: + ∂x ∂y ∂z r r r r r r φS ( E ) = ∫ dφ = ∫ E ⋅ dS = ∫ divE ⋅ dV = ∫ (∇ ⋅ E ) ⋅ dV that is the statement.
φ S V V

z

Bibliography:

---------------------------------

1) ( L. Rubino) http://vixra.org/pdf/1201.0002v1.pdf Thank you for your attention. Leonardo RUBINO
leonrubino@yahoo.it

Sign up to vote on this title
UsefulNot useful